TYPE OF LITTER AND THE INCIDENCE OF LESION IN BROILERS' CARCASS - GARCIA, Rodrigo Garófallo; CALDARA, Fabiana Ribeiro; NÄÄS, Irenilza de Alencar; DUARTE, Nilsa Silva (Revista Brasileira de Engenharia de Biossistemas, 2011)
The objective of this study was to evaluate the compaction of the bed; feathering and incidence of lesions in carcasses of broilers raised on different types of beds. Shavings;; 2592 day old chicks sexed Ross® the line were distributed in randomized in a factorial 2 x 6,, being two sexes (male and female) and six substrates bed (Sugar cane bagasse were used Bark rice, Napier grass, sugar cane bagasse + rice husks and sugarcane bagasse + Shavings). Was evaluated weekly compacting the poultry house litter, using a penetrometer. At 31, 38 and 45 days of age evaluated the warping of back and thigh of birds, assigning grades 0-10, according to the degree of warping. At 42 days the chicks were killed and identified the presence of bruises, scratches, dermatitis and footpad lesions. There was no influence of the type of bed in the incidence of scratches, bruises, injuries and footpad dermatitis. The highest incidence of footpad lesions occurred in birds reared on Napier bed and the smallest, those housed on Shavings. Sex significantly influenced the incidence of dermatitis and footpad lesions, with males being more affected than females.